Information seeking and retrieval systems: Components and evolution - Codina, LLuís (Anuario ThinkEPI, 2018)
A description and presentation of the universal components of information seeking and retrieval systems including query system, search results page, and record (metadata) model. Bibliographic information systems as an environment for bibliographic retrieval systems is considered. The main trends in the recent evolution of user interfaces in the case of academic databases are discussed.